Pediatric Behçet’s disease: Experience of a single tertiary center - Ceyhun Açarı,; Rana İşgüder,; Rüya Torun,; Balahan Makay,; Şevket Erbil Ünsal, (Archives of Rheumatology, 2023)
Objectives: The aim of this study was to examine the clinical and phenotypic features of pediatric Behçet’s disease (PEDBD) in our clinic and present the rates of fulfilling the diagnostic criteria. Patients and methods: Thirty-four patients (20 males, 14 females; mean age: 16.0±2.1 years; range, 10 to 18 years) diagnosed with PEDBD between January 2010 and December 2019 were retrospectively evaluated. Patients were reclassified according to 1990 International Study Group (ISG) criteria, 2014 International Criteria for Behçet’s Disease (ICBD), and PEDBD criteria. Results: The mean age at diagnosis was 12.6±3.1 years, the median diagnosis delay time was 12.0 (range, 4.5 to 27.0) months, and the mean age at symptom onset was 10.8±2.9 years. The mean follow-up period was 31.9±20.9 months. Oral aphthous ulcer was observed in 33 (97.1%), genital ulcer in 16 (47.0%), ocular involvement in 15 (44.1%), skin lesion in 11 (32.3%), joint involvement in nine (26.4%), both vascular and neurological involvement in six (17.6%) patients. The pathergy test was positive in 11 (37.8%) patients, and human leukocyte antigen (HLA)-B51 was positive in 11 (78.5%) of 14 patients. The rates of patients meeting the criteria for ISG, ICBD, and PEDBD were 52.9%, 82.4%, and 50.0%, respectively. Conclusion: Pathergy and HLA-B51 can be used as supportive findings in patients who do not meet the diagnostic criteria. However, expert opinion is still the gold standard in diagnosis.